Detection of Receptor and Synthesis Antagonists of Platelet Activating Factor in Human Whole Blood and Neutrophils Using Luminol-Dependent Chemiluminescence - K. VanDyke; V. Castranova (The National Institute for Occupational Safety and Health (NIOSH), 1989)
"INTRODUCTION A soluble mediator has been described which is released from activated rabbit leukocytes and induces histamine secretion from rabbit platelets (Barbaro and Zvaifler, 1966; Siraganian and Osler, 1971). This factor has been isolated, characterized and named platelet activating factor, PAF (Bcnveniste et. al., 1972). PAF has since been chemically identified as l-0-alkyl-2-acetyl-sn-glyceryl-3-phosphocholine (Benveniste et. al., 1979; Demopoulous et. al., 1979).PAF is a lipid mediator of broad biological activity. It causes smooth muscle contraction, contraction of lung tissue and decreased FEV 1; while enhancing capillary permeability thus causing edema (Pinkard, 1983). In addition, PAF is a chemoattractant and can lead to inflammation.PAF has been reported to stimulate the release of lysosomal enzymes, leukotriene B,, and lipid metabolites from neutrophils (Smith et. al., 1983; Shaw et. al., 1981; Lin et. al., 1982; O'Flaherty et. al., 1984). The objective of the present investigation was to further characterize PAP-induced stimulation of granulocytes and to develop a bioassay, i.e. chemiluminescence, for screening PAF receptor antagonists and inhibitors of PAP-induced activation of granulocytes. The possible use of the chemiluminescence assay to monitor PAF synthesis by human granulocytes is also described.METHODSBlood was drawn from healthy volunteers into a blood storage bag containing CPD anticoagulant. Granulocytes were partially purified by dextran sedimentation and further purified by centrifugal elutriation as described previously (Jones et. al., 1980). Granulocytes obtained by this procedure were approximately 95 percent pure. The number of granulocytes in this preparation was determined using an electronic cell counter (Coulter Model Z1, Coulter Instrument Co., Hialeah, FL). Isolated granulocytes were used to monitor membrane potential, hydrogen peroxide and superoxide release, oxygen consumption, calcium uptake and, in some cases, chemiluminescence. Studies of PAF receptor antagonists were conducted using neutrophils isolated by density centrifugation. Briefly, blood was layered onto Mono-Poly-Resolving Medium (Flow Laboratories, McLean, VA) and centrifuged at 22 °C and 300 g for 30 min. Neutrophils collected from the second band of this gradient were at least 90 percent pure."